Comparing deep eutectic solvents and cyclodextrin complexes as curcumin vehicles for blue‑light antimicrobial photodynamic therapy approaches - Silva, Eduardo (2022)
Curcumin (Cur), a polyphenolic compound derived from Curcuma longa L., has garnered the attention of the scientifc community due to its remarkable biological properties such as its potential as a photosensitizing agent for photodynamic therapy (PDT). However, due to its low solubility in aqueous media and instability at physiological and alkaline pH, Cur has struggled to fnd relevant clinical application. To tackle these shortcomings, two distinct Cur-based formulations based on either complexation with methyl-Î²-cyclodextrin (MÎ²CD), MÎ²CDC-Cur, or dissolution in a choline chloride (ChCl): glycerol (Gly) deep eutectic solvent (DES), DES-Cur, were produced, physio-chemically characterized and compared regarding their potential as phototherapeutic agents for blue-light antimicrobial photodynamic therapy (aPDT) approaches. Both MÎ²CD-Cur and DES-Cur were able to greatly enhance Cur solubility profle when compared to Cur powder. However, MÎ²CD-Cur appears to hinder some of Curâ s basal biological properties and possessed greater basal cytotoxicity towards L929 murine fbroblast cell line. Furthermore, MÎ²CD-Cur was less photo-responsive when exposed to light which may hamper its application in blue-light aPDT approaches. In contrast, DES-Cur showed good biological properties and high photoresponsivity, displaying relevant phototoxicity against bacterial pathogens (â ¥99.9% bacterial reduction) while being better tolerated by L929 murine cells. Overall, this study found DES to be the more efective vehicle for Cur in terms of phototherapeutic potential which will serve as basis to develop novel platforms and approaches for blue-light aPDT targeting localized superfcial infections.